Meta-analysis and trial sequential analysis of shexiang baoxin pill for coronary slow flow - Guo, Hongxin; Li, Xingyuan; Zhu, Mingjun (Frontiers in Pharmacology, 2022)
Background: Coronary slow flow (CSF) is a common cardiovascular phenomenon with no effective treatment in conventional Western medicine (CWM). Shexiang Baoxin Pill (SXBXP) is a widely used Chinese medicine for cardiovascular disease in China, and clinical studies have shown that it has good efficacy for CSF. Objective: To systematically evaluate the efficacy and safety of SXBXP for CSF. Methods: Seven databases were searched to identify related randomized controlled trials (RCTs). The Meta-analysis, trial sequential analysis (TSA), and Grades of Recommendation, Assessment, Development and Evaluation (GRADE) were performed using Stata 14.1, TSA 0.9.5.10 Beta and GRADE profiler 3.2.2 software respectively. Results: A total of 10 RCTs were included. Meta-analysis showed that compared with CWM treatment alone, SXBXP combined with CWM further improved the angina pectoris efficacy [RR = 1.37, 95% CI (1.23, 1.52), P < 0.000 01] and nitric oxide (NO) level [WMD = 11.32, 95% CI (0.04, 22.59), P = 0.049], decreased the mean corrected TIMI frame count (CTFC) [WMD = -4.23, 95% CI (-5.51, -2.95), P < 0.000 01], CTFC of the left anterior descending artery (LAD) [WMD = -6.36, 95% CI (-12.07, -0.65), P = 0.029], left circumflex artery (LCX) [WMD = -5.73, 95% CI (-8.79, -2.67), P < 0.000 01], and right coronary artery (RCA) [WMD = -6.72, 95% CI (-10.60, -2.84), P = 0.001], decreased the positive rate of treadmill exercise test [RR = 0.45, 95% CI (0.25, 0.83), P = 0.010], endothelin-1 (ET-1) level [WMD = -11.03, 95% CI (-13.92, -8.14), P < 0.000 01], high-sensitivity C-reactive protein (hs-CRP) [WMD = -1.95, 95% CI (-2.57, -1.34), P < 0.000 01], and adverse reactions [RR = 0.20, 95% CI (0.05, 0.85), P = 0.030]. The GRADE evidence quality rating presented with moderate, low or very low quality of evidence. TSA further affirmed the clinical efficacy. Conclusion: Although some results suggest that there may be a positive effect of SXBXP for CSF, the quality of the primary study including the reporting is too poor and therefore, no benefits could be demonstrated. More high-quality studies are still needed to further confirm the efficacy and safety.